Assessment of incidence of post-operative wound infection in women undergoing caesarean section: a retrospective study - Sangavi, Radha; K. S., Rajkumari (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The surgical site infection is the second most common infectious complication occurring after caesarean section. Infections occurring after caesarean section represent a considerable burden to the healthcare systems and preventing these complications is a priority of healthcare systems especially in developing countries. The aim of this study was to determine the incidence of SSI in patients undergoing a LSCS at a RIMS teaching hospital, Raichur, and to identify risk factors, common bacterial pathogens and antibiotic sensitivity. Methods: The present retrospective study was conducted in RIMS Institute, during a period of 3 years i.e. from 2013-2016. In this study a total of 50 cases were collected from MRD department. They were divided into two groups- cases and controls, each having 50 subjects each. Wound infection was defined as inflammation or sepsis with or without positive bacterial cultures. With SSI, there may be fever, redness, swelling and/or pain in the area around the incision site. Complete information regarding demographic data, the type and indication for caesarean section, duration of labour, duration of surgery and rupture of membrane were recorded. Wound infections occuring after 30 days of LSCS & other gynaecological surgeries were excluded. All the results were analyzed by SPSS software 16.0. Chi-square test and student t test were used for the assessment of level of significance. Probability value of less than 0.05 was considered significant. Results: A total of 100 subjects were included in the present study, out of which, 50 were cases and the remaining 50 were controls. The mean age of the subjects was 37.45 years. There were 7 cases and 13 controls who were aged between 20-24 years. There was no significant difference amongst cases and controls regarding age. There was a significant difference in the haemoglobin levels amongst cases and controls. The third criterion that was assessed was duration of labour. Majority of the cases had prolonged labour whereas in majority of the controls, the duration of labour of labour was less than 6 hours. There was a significant difference in duration of labour amongst cases and controls (p<0.05). Elective c section was done in 2 cases and 6 controls. C section was performed in an emergency in 48 cases and 44 controls. There was a significant difference in the operation time between cases and controls (p<0.05). E.coli infection occurred in 15 cases in the present study followed by Actinobacter species which occurred in 13 cases. Absence of growth was seen in 5 cases. Conclusions: The risk factors associated with SSI in our study were, haemoglobin levels, prolonged labour, duration of operation. The most common organisms isolated were E. coli and Actinobacter species.